Analisis Kecurangan Laporan Keuangan dan Pelanggaran Etika Profesi yang Mempengaruhi Kepercayaan Publik Terhadap Kinerja Perusahaan - Azzahara Rahmah; Pina Nuraeni; Nadila Nurazizah (Teewan Journal Solutions, 2025)
This study aims to analyze the influence of financial statement fraud and violations of professional accounting ethics on the level of public trust in corporate performance, using a case study of PT Asuransi Jiwasraya (Persero). The method used is a descriptive qualitative approach with the unit of analysis being social phenomena. Data were collected through literature review and indirect observation of financial reports and relevant academic publications. This research employs the Fraud Pentagon theory, which includes five main factors that drive fraud: pressure, opportunity, rationalization, capability, and arrogance. In addition, principles of professional accounting ethics such as honesty, responsibility, and accountability are used to assess the integrity of the perpetrators. The findings show that fraud in Jiwasraya’s financial statements occurred systemically and was exacerbated by weak internal controls and low ethical awareness in the work environment. These conditions led to a significant decline in public trust toward the company and the national financial industry in general. This study contributes to a broader understanding of the relationship between fraud, professional ethics, and public trust, and highlights the importance of strengthening governance and ethical value systems in the financial services sector.